Classification Trends In Nicknames And Titles In Arab Cultural Heritage/ اتجاهات تصنيف الكني والألقاب في التراث الثقافي العربي - Khalid Bin Hassan AlAbri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to compile an index of works written on kunya (pseudonyms), titles, and pseudonyms, found in biographical dictionaries, hadith literature, sabaqat (generational classifications), and historical writings, as well as in the works of Arabic writers, poets, and linguists. This study highlights the most important works reflecting this scholarly interest and demonstrates the diversity of these writings, including those specifically addressing kunya and titles. This study adopts a descriptive methodology based on describing the phenomenon under study, collecting relevant data and information about it, and drawing conclusions that help clarify important aspects of this type of work and writing. This study also surveys and examines the works of early Arab scholars without addressing contemporary writings.